Beautiful sacrifice eaudiobook - Lowell, Elizabeth (Recorded Books Inc., 2012)
With over 20 million copies of her novels in print, New York Times best-selling author Elizabeth Lowell has proven to be a formidable voice in romantic suspense. Beautiful Sacrifice stars archaeologist Lina Taylor, who is tapped by former ICE officer Hunter Johnson to help recover stolen Mayan artifacts. As the two dig deeper into the mystery, their mutual attraction becomes irresistible-but a sinister death cult lurks in the shadows, ready to pounce should the couple get too close to the answers they seek.